Influence of Specially-Organized Theoretical and Practical Physical Training Classes on Formation of Professional and Personal Qualities of Students - V Y Sokolov; K A Kolosov; V E Yakunin (Peoples' Friendship University of Russia (RUDN University), 2012)
The work analyses the influence of the developed specially organized physical training classes on the formation of psycho-physiological and psychological functions of the students concerning their professional work.